Assessment of ecological risk of soil contamination by heavy metals - V. L. Bezsonnyi; A. N. Nekos; O. O. Gololobova (Вісник Харківського національного університету імені В.Н. Каразіна: Серія Екологія)
Purpose. To assess the ecological risk of soil contamination by heavy metals and analyze their concentrations in protected areas in the Zmiivska community of the Kharkiv region and the impact zone of the Zmiivska TPP.